Characterization of the Campylobacter jejuni Population in the Barnacle Geese Reservoir. (20th June 2014) - Llarena, A.‐K.; Skarp‐de Haan, C. P. A.; Rossi, M.; Hänninen, M.‐L.
Summary Campylobacter spp. are the most common cause of bacterial gastroenteritis worldwide and have been isolated from a wide number of different hosts and environmental sources. Waterfowl is considered a natural reservoir for this zoonotic bacterium and may act as a potential infection source for human campylobacteriosis. In this study, faecal samples from 924 barnacle geese were tested for the presence of C. jejuni and C. coli. The resulting C. jejuni and C. coli populations were characterized by multilocus sequence typing (MLST), structure analysis by BAPS and phylogenetic analysis based on full genome sequences. The prevalences of C. jejuni in barnacle geese faeces were 11.5% and 23.1% in 2011 and 2012, respectively, and only 0.2% of the samples were positive for C. coli in both years. Furthermore, a possible adaption of the clonal complexes (CCs) ST‐702 and ST‐1034 to the barnacle geese reservoir was found, as these two CCs represented the majority of the typed isolates and were repeatedly isolated from different flocks at several time‐points. Further core genome phylogenetic analysis using ClonalFrame revealed a formation of a distinct monophyletic lineage by these two CCs, suggesting a certain degree of clonality of the C. jejuni population adapted to barnacle geese. Therefore, although STs also commonly found in humans patients (e.g. ST‐45) were among the barnacle geese C. jejuni isolates, this reservoir is probably an infrequent source for human campylobacteriosis.